The Organization of Knowledge in Multinational Firms - Anna Gumpert (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
This paper provides the first in-depth study of the organization of knowledge in multinational firms. In the theory, knowledge is a costly input for firms that they can acquire at their headquarters or their production plants. Communication costs impede the access of the plants to headquarter knowledge. The model shows that multinational firms systematically acquire more knowledge at both their foreign and domestic plants than non-multinationals if their foreign plants face higher communication costs with headquarters than their domestic plants. This theoretical prediction helps understand why multinational firms pay higher wages to workers than non-multinational firms, and why their sales decrease across space. The empirical analyses show that higher communication costs indeed decrease multinational firmsf́oreign sales. Consistent with model-specific comparative statics, the decrease is stronger in sectors with less predictable production processes. Novel data on corporate transferees allow shedding light on one tool of multinational firmsórganization of knowledge.
Keywords: D21; D24; F21; F23; 330; multinational firm; knowledge hierarchy; organization; geography of FDI; multinational wage premium; corporate transferees